The Effect of Implementing Learning Models Contextual Teaching and Learning (CTL) toward Students’ Science Learning Outcomes of Class IV Cluster Ii at Donggo, Bima Regency - Yuningsih, Yuyun (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research is an experimental study with a nonequivalent control group design which aims to determine: (1) An overview of the science learning model at SD Gugus II, Donggo District, Bima Regency (2) An overview of the application of science learning in SD Class IV Cluster II, Donggo District, Bima Regency using the model Contextual Teaching and Learning (CTL). (3) Overview of the learning outcomes of Class IV Science at Gugus II Elementary School, Donggo District, Bima Regency. (4) The effect of Contextual Teaching and Learning (CTL) model learning on Science Class IV Gusus II learning outcomes, Donggo District, Bima Regency. The population in this study were fourth grade students in Cluster II, Donggo District, Bima Regency, which consisted of SDN Inpres O'o, SDN O'o (Mpili), SDN Kamunti, SDN Inpres Kala, and SDN Manggekompo with a total of 74 students. While the samples used in this study were class IV SDN Kamunti as a control class, totaling 20 people and class IV at SDN Inpres O'o as an experimental class, totaling 23 people. The data from this study were obtained from learning outcomes tests with the subject matter of motion and style in the form of pretest and posttest as well as teacher and student activity observation sheets. The data analysis technique in this research is descriptive and inferential analysis. The results showed that: (1) The science learning model used in SD Gugus II, Donggo District, Bima Regency, was a lecture and group discussion learning model. (2) The application of Contextual Teaching and Learning (CTL) model learning in class IV SD Gugus II, Donggo District, Bima Regency has been in accordance with the implementation of learning where the teacher's teaching activities are in accordance with the set plan and the positive activity of students is high when compared to the previous implementation of the learning model Contextual Teaching and Learning (CTL). (3) The science learning outcomes of the control class (SDN Kamunti) students who applied the conventional learning model were lower than the results of the experimental class that applied the Contextual Teaching and Learning (CTL) learning model. (4) the application of the Contextual Teaching and Learning (CTL) learning model has a significant effect on the fourth grade science learning outcomes of SD Gugus II, Donggo District, Bima Regency. This is evidenced by the results of the Independent t-test. The t-test value is 5.344 and the t-table value is 2.019.